ANALITYCAL REVIEW: THE DYNAMICS OF ISLAMIC THEOLOGY FROM THE KHAWARIJ TO INCLUSIVE THEOLOGY - Shintia Mulyawati; Zulbaidah Zulbaidah; Duski Samad; Firdaus ST Mamad (STAI Darul Qalam Tangerang, 2025)
This article explores the dynamics of Islamic theology by examining the conceptual development of major theological schools from the Khawarij to contemporary thought. The study seeks to illuminate their historical emergence, intellectual frameworks, and the transformation of doctrinal positions across different periods of Islamic history. Using a literature-based research method, this work analyzes classical theological texts alongside modern scholarly interpretations. The findings reveal that each theological tradition was shaped by distinctive social, political, and intellectual circumstances, resulting in diverse perspectives on human agency, divine justice, and the role of religion in public life. The discussion further demonstrates that contemporary Islamic theology increasingly adopts critical, dialogical, and human-centered approaches in response to modern challenges. Overall, the study highlights the adaptive and evolving character of Islamic theology in engaging with changing societal contexts.